First Civilizations : ancient Mesopotamia and ancient Egypt - Chadwick, Robert, 1941- (Equinox, 2005)
First Civilizations is the second edition of a popular student text first published in 1996 in Montreal by Les Editions Champ Fleury. This much updated and expanded edition provides an introductory overview of the civilizations of ancient Mesopotamia and ancient Egypt. Itwas conceived primarily for students who have little or noknowledge of ancient history or archaeology. The book begins with the role of history and archaeology inunderstanding the past, and continues with the origins of and the formation of the Sumerian city-states in Mesopotamia. Three subsequent chapters conce /